Respuesta :

caylus
hello,

14bx²-7x^3-4b+2x= -7x^3+14bx²+2x-4b
=-7x²(x-2)+2(x-2b)
=(x-2b)(-7x²+2)
=(2b-x)(7x²-2)

answer 2

Answer:

[tex](2b-x)(7x^2-2)[/tex]

Step-by-step explanation:

We have to factor the expression [tex]14bx^2-7x^3-4b+2x[/tex]

We apply the method of grouping to factor it.

Make groups

[tex](14bx^2-7x^3)+(-4b+2x)[/tex]

Take GCF

[tex]7x^2(2b-x)-2(2b+x)[/tex]

Finally, factored out the common factor

[tex](2b-x)(7x^2-2)[/tex]

The factored form of the given expression is

[tex](2b-x)(7x^2-2)[/tex]